Advances in understanding interferon-mediated immune responses to enteric viruses in intestinal organoids - Nolan, Lila S.; Baldridge, Megan T. (Frontiers in Immunology, 2022)
Interferons (IFN) are antiviral cytokines with critical roles in regulating pathogens at epithelial barriers, but their capacity to restrict human enteric viruses has been incompletely characterized in part due to challenges in cultivating some viruses in vitro, particularly human norovirus. Accordingly, advancements in the development of antiviral therapies and vaccine strategies for enteric viral infections have been similarly constrained. Currently emerging is the use of human intestinal enteroids (HIEs) to investigate mechanisms of human enteric viral pathogenesis. HIEs provide a unique opportunity to investigate host-virus interactions using an in vitro system that recapitulates the cellular complexity of the in vivo gastrointestinal epithelium. This approach permits the exploration of intestinal epithelial cell interactions with enteric viruses as well as the innate immune responses mediated by IFNs and IFN-stimulated genes. Here, we describe recent findings related to the production, signaling, and function of IFNs in the response to enteric viral infections, which will ultimately help to reveal important aspects of pathogenesis and facilitate the future development of therapeutics and vaccines.